2015
DOI: 10.4103/1658-354x.152885
|View full text |Cite
|
Sign up to set email alerts
|

Influence of GlideScope assisted endotracheal intubation on intraocular pressure in ophthalmic patients

Abstract: Background:Traditional Macintoch laryngoscopy is known to cause a rise in intraocular pressure (IOP), tachycardia and hypertension. These changes are not desirable in patients with glaucoma and open globe injury. GlideScope is a video laryngoscope that functions independent of the line of sight, reduces upward lifting forces for glottic exposure and requires less cervical neck movement for intubation, making it less stimulating than Macintosh laryngoscopy.Aim:The aim was to assess the variations in IOP and hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Twelve of these studies were excluded because they did not investigate hemodynamic response (n = 5), compared laryngoscopes other than the GlideScope and Macintosh (n = 6), or involved use of a double-lumen tube (n = 2). Thirteen trials [ 10 , 21 32 ] were confirmed to meet the inclusion criteria (Fig. 1 ) and are summarized in detail in Table 1 (see Table 1 , which illustrates the characteristics of trials included in this meta analysis).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve of these studies were excluded because they did not investigate hemodynamic response (n = 5), compared laryngoscopes other than the GlideScope and Macintosh (n = 6), or involved use of a double-lumen tube (n = 2). Thirteen trials [ 10 , 21 32 ] were confirmed to meet the inclusion criteria (Fig. 1 ) and are summarized in detail in Table 1 (see Table 1 , which illustrates the characteristics of trials included in this meta analysis).…”
Section: Resultsmentioning
confidence: 99%
“…Eight trials were for patients with American Society of Anesthesiologists-Physical Status classification 1-2. [ 10 , 21 , 25 – 30 ] There were 4 trials including American Society of Anesthesiologists-Physical Status classification 3 patients. [ 22 – 24 , 31 ] In our study, 11 out of 13 trials were tracheal intubated with oral intubation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations